Combustion characteristics of gasoline DICI engine in the transition from HCCI to PPC: Experiment and numerical analysis. (15th October 2019) - Xu, Leilei; Bai, Xue-Song; Li, Changle; Tunestål, Per; Tunér, Martin; Lu, Xingcai
Abstract: Both numerical simulations and experiments were conducted in a heavy-duty DICI engine, with PRF81 as a gasoline surrogate, to investigate how the fuel stratification, auto-ignition and combustion are affected by the start of injection (SOI). The intake air temperature was adjusted to keep the combustion phasing constant when the SOI was swept from − 100 to − 20 o CA ATDC, covering different regimes of combustion, from HCCI to PPC. It is found that in the HCCI regime the combustion process is less sensitive to the variation of SOI since the fuel/air mixture is fairly homogeneous. The fuel/air mixture is under fuel-lean condition and the required intake temperature for a constant CA50 is the highest. In the PPC regime there is an optimal SOI window, within which the required intake temperature is the lowest to maintain a constant CA50 and the engine thermal efficiency is the highest. The optimal operation window starts at the SOI when all fuel is injected into the piston bowl and ends when the fuel injection is towards the bottom wall of the piston bowl, which results in a high heat transfer losses. The SOI window for optimal engine operation is expected to be fuel injector and piston bowl geometry dependent. During the transition regime, the fuel is injected towards the piston head in the squish region. The combustion process is highly sensitive to SOI due to the high sensitivity of fuel distribution in the cylinder to SOI. The engine thermal efficiency is the lowest due to the incomplete oxidation of fuel in the squish region. Highlights: Fuel stratification and combustion characteristics affected by the SOI and engine geometry were systematically studied. The transition regime from HCCI to PPC and fuel stratification level during the SOI swept were defined. The mechanisms behind the non-monotonic dependence of intake temperature on SOI were investigated. The sensitivity of the in-cylinder wall temperature for the different combustion regime was evaluated. For a given constant combustion phasing, an optimal SOI window was found.